Frequency and Gram Categorywise Distribution of Clinical Isolates from Patient samples in tertiary care Hospital of Lahore - Abbas, Ansar; Kausar, Humera; Hasnain, Ammarah; Kabir, Mahvish; Siddiqui, Maria Fareed (MARKHOR (The Journal of Zoology), 2021)
Antibiotics form an important tool in the treatment of various bacterial infections but their overuse and misuse are resulting in antibacterial resistance among bacteria. Objective: to outline the frequency and gram categorywise distribution of clinical isolates from patient samples Methods: In this study, 1000 samples were collected from the patients attending the pathology department of Fatima memorial hospital, Lahore, Pakistan. Identification of bacteria was done through conventional culture and biochemical tests Results: one thousand clinical isolated were identified Conclusions: Gram negative bacterial isolates were prevalent, with 55% frequency distribution and Staphylococcus aureus was frequent as it was identified in 410 different samples of patients.